2016
DOI: 10.1080/00071668.2016.1236362
|View full text |Cite
|
Sign up to set email alerts
|

Genetic evaluation of weekly body weight in Japanese quail using random regression models

Abstract: 1. A total of 11 826 records from 2489 quails, hatched between 2012 and 2013, were used to estimate genetic parameters for BW (body weight) of Japanese quail using random regression models. Weekly BW was measured from hatch until 49 d of age. WOMBAT software (University of New England, Australia) was used for estimating genetic and phenotypic parameters. 2. Nineteen models were evaluated to identify the best orders of Legendre polynomials. A model with Legendre polynomial of order 3 for additive genetic effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 33 publications
2
5
0
1
Order By: Relevance
“…Arango et al (2004) reported decreasing influence of permanent environmental effects and increasing additive genetic effects for mature cow body weights over time. Additive genetic and permanent environmental variances both increased in random regression analyses of observed days to weight in fed cattle (Speidel et al, 2016), and estimates of heritability for BW in quail increased with age (Karami et al, 2017). The present study indicated increasing c 2 and decreasing h 2 over time, suggesting an increasing influence of environmental and decreasing relative influence of additive genetic effects on EV with increasing age.…”
Section: Random Regressionsupporting
confidence: 54%
“…Arango et al (2004) reported decreasing influence of permanent environmental effects and increasing additive genetic effects for mature cow body weights over time. Additive genetic and permanent environmental variances both increased in random regression analyses of observed days to weight in fed cattle (Speidel et al, 2016), and estimates of heritability for BW in quail increased with age (Karami et al, 2017). The present study indicated increasing c 2 and decreasing h 2 over time, suggesting an increasing influence of environmental and decreasing relative influence of additive genetic effects on EV with increasing age.…”
Section: Random Regressionsupporting
confidence: 54%
“…Egg productions at different age intervals were positively correlated. Phenotypic and genetic correlations between adjacent periods of egg production were more closely correlated than remote periods (Karamia et al, 2017). The egg weights were also highly correlated traits with egg weights at different time intervals.…”
Section: Phenotypic and Genetic Correlationsmentioning
confidence: 81%
“…In agreement with the current findings, Silva et al (2013) reported that genetic and phenotypic correlations between weekly BW of Japanese quail were 0.35 to 0.96 and 0.17 to 0.80, respectively. In contrast, Karami et al (2017) revealed a higher estimated genetic correlation of 0.85, 0.90 and 0.91 between BW0 with BW7, BW14 and BW21, respectively, in Japanese quail through a random regression model. Estimated h 2 for BWG at different ages tended to be low, varying from 0.18 (BWG 4-6) to 0.23 (BWG 0-6).…”
Section: Resultsmentioning
confidence: 81%
“…These findings could encourage the breeders to practise genetic selection at an early age in Japanese quail. In contrast, Saatci et al (2003), Nasiri Foomani et al 2014, and Karami et al (2017) found that heritability values for BW of Japanese quail tended to increase with age. The estimated heritabilities (h 2 ) and genetic and phenotypic correlations of BW and BWG of Japanese quail are shown in Table 3.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation